Pengaruh Pengenaan Bea Materai Dan Kemudahan Teknologi Investasi Terhadap Minat Investasi Yang Dimoderasi Oleh Sosial Media Edukasi Saham - Putra, Rio Johan; Qodary, Hilwa Fithratul (Universitas 17 Agustus 1945 Jakarta, 2021)
This study aims to examine the effect of stamp duty and ease of investment technology on investment interest moderated by stock education social media. The population in this study is the general public who invests in stocks. The sampling method used in this study was random sampling. The method of determining the number of samples in this study is 5-10 times the number of indicators. This research uses Confirmatory Factor Analysis test and hypothesis testing using Lisrel software. Based on the test results, it is concluded that the imposition of stamp duty and the ease of investment technology has no effect on investment interest. And for social media, stock education has a negative effect on investment interest. In addition, social media for stock education strengthens the effect of ease of investment technology on investment interest.Keywords: Stamp Duty, The Ease of Investment Technology, Investment Interest, Social Media